Search for heavy neutrinos and third-generation leptoquarks in hadronic states of two leptons and two jets in proton-proton collisions at root s=13 TeV - Sirunyan, A. M. (2019)
A search for new particles has been conducted using events with two high transverse momentum leptons that decay hadronically and at least two energetic jets. The analysis is performed using data from proton-proton collisions at 13 TeV, collected by the CMS experiment at the LHC in 2016 and corresponding to an integrated luminosity of 35.9 fb(-1). The observed data are consistent with standard model expectations. The results are interpreted in the context of two physics models. The first model involves right-handed charged bosons, W-R, that decay to heavy right-handed Majorana neutrinos, N ( = e, , ), arising in a left-right symmetric extension of the standard model. The model considers that N-e and N are too heavy to be detected at the LHC. Assuming that the N mass is half of the W-R mass, masses of the W-R boson below 3.50 TeV are excluded at 95% confidence level. Exclusion limits are also presented considering different scenarios for the mass ratio between N and W-R, as a function of W-R mass. In the second model, pair production of third-generation scalar leptoquarks that decay into bb is considered, resulting in an observed exclusion region with leptoquark masses below 1.02 TeV, assuming a 100% branching fraction for the leptoquark decay to a lepton and a bottom quark. These results represent the most stringent limits to date on these models.